Can a finding of cervical vestibular evoked myogenic potentials contribute to vestibular migraine diagnostics? - Tihana Vešligaj; Siniša Maslovara (Medicinski glasnik, 2016)
Aim: To investigate differences in vestibular evoked myogenic potentials (VEMP) results with patients suffering from vestibular migraine and healthy people, taking into consideration values of threshold and latency of occurrence of the characteristic wave complex, size of amplitude, and interaural amplitude ratio. According to the results, determine the importance and usefulness of VEMP in vestibular migraine diagnostics. Methods: A total number of 62 subjects were included in the study, 32 of them belonging to a group of patients suffering from vestibular migraine (VM), while other 30 were in a control group of healthy subjects. Information was collected during the diagnostic evaluation. General and otoneurological history of patients and bedside tests, audiological results, videonystagmography and cervical vestibular evoked myogenic potentials (cVEMP) were made. Results: There was a difference in an interaural ratio of amplitudes in the experimental and control groups, but it was not found to be clinically significant. By ToneBurst 500 Hz method, the interaural amplitude ratio higher than 35% was measured in 46.97% subjects, while the response was totally unilaterally missing in 28.8% patients. Conclusion: Even the sophisticated method as cVEMP does not give the ultimate result confirming the vestibular migraine diagnosis, and neither do other diagnostic methods. cVEMP result can contribute to the completion of full mosaic of vestibular migraine diagnostics.
Keywords: vertigo; migraine; diagnosis